PREDICTING ANIMAL δ18O: ACCOUNTING FOR DIET AND PHYSIOLOGICAL ADAPTATION - Kohn M.J. (My University, 1996)
Theoretical predictions and measured isotope variations indicate that diet and physiological adaptation have a significant impact on animals δ18O and cannot be ignored. A generalized model is therefore developed for the prediction of animal body water and phosphate δ18O to incorporate these factors quantitatively. Application of the model reproduces most published compositions and compositional trends for mammals and birds. A moderate dependence of animal δ18O on humidity is predicted for drought-tolerant animals, and the correlation between humidity and North American deer bone composition as corrected for local meteoric water is predicted within the scatter of the data. In contrast to an observed strong correlation between kangaroo δ18O and humidity (Δδ18O/Δh ~ 2.5 +/- 0.4%%/10% r.h.), the predicted humidity dependence is only 1.3 - 1.7%%/10% r.h., and it is inferred that drinking water in hot dry areas of Australia is enriched in 18O over rainwater. Differences in physiology and water turnover readily explain the observed differences in δ18O for several herbivore genera in East Africa, excepting antelopes. Antelope models are more sensitive to biological fractionations, and adjustments to the flux of transcutaneous water vapor within experimentally measured ranges allows their δ18O values to be matched. Models of the seasonal changes of forage composition for two regions with dissimilar climates show that significant seasonal variations in animal isotope composition are expected, and that animals with different physiologies and diets track climate differently. Analysis of different genera with disparate sensitivities to surface water and humidity will allow the most accurate quantification of past climate changes.